Psychiatric readmissions and their association with environmental and health system characteristics: a systematic review of the literature. Issue 1 (December 2016) - Kalseth, Jorid; Lassemo, Eva; Wahlbeck, Kristian; Haaramo, Peija; Magnussen, Jon
Abstract Background Psychiatric readmissions have been studied at length. However, knowledge about how environmental and health system characteristics affect readmission rates is scarce. This paper systemically reviews and discusses the impact of health and social systems as well as environmental characteristics for readmission after discharge from inpatient care for patients with a psychiatric diagnosis. Methods Comprehensive literature searches were conducted in the electronic bibliographic databases Ovid Medline, PsycINFO, ProQuest Health Management and OpenGrey. In addition, Google Scholar was utilised. Relevant publications published between January 1990 and June 2014 were included. No restrictions regarding language or publication status were imposed. A qualitative synthesis of the included studies was performed. Variables describing system and environmental characteristics were grouped into three groups: those capturing regulation, financing system and governance; those capturing capacity, organisation and structure; and those capturing environmental variables. Results Of the 734 unique articles identified in the original search, 35 were included in the study. There is a limited number of studies on psychiatric readmissions and their association with environmental and health system characteristics. Even though the review reveals an extensive list of characteristics studied, most characteristics appear in a very limited number of articles. The most frequently studied characteristics are related to location (local area, district/region/country). In most cases area differences were found, providing strong indication that the risk of readmission not only relates to patient characteristics but also to system and/or environmental factors that vary between areas. The literature also points in the direction of a negative association of institutional length of stay and community aftercare with readmission for psychiatric patients. Conclusion This review shows that analyses of system level variables are scarce. Furthermore they differ with respect to purpose, choice of system characteristics and the way these characteristics are measured. The lack of studies looking at the relationship between readmissions and provider payment models is striking. Without the link to provider payment models and other health system characteristics related to regulation, financing system and governance structure it becomes more difficult to draw policy implications from these analyses.